If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 = 7v + -8 + -2v Reorder the terms: -3 = -8 + 7v + -2v Combine like terms: 7v + -2v = 5v -3 = -8 + 5v Solving -3 = -8 + 5v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-5v' to each side of the equation. -3 + -5v = -8 + 5v + -5v Combine like terms: 5v + -5v = 0 -3 + -5v = -8 + 0 -3 + -5v = -8 Add '3' to each side of the equation. -3 + 3 + -5v = -8 + 3 Combine like terms: -3 + 3 = 0 0 + -5v = -8 + 3 -5v = -8 + 3 Combine like terms: -8 + 3 = -5 -5v = -5 Divide each side by '-5'. v = 1 Simplifying v = 1
| 12x-4(5y-2x)=40 | | 2x+4=12-x-5 | | y^2+7y-14=0 | | -2y-4(-0.25+-0.5x)=1 | | -9/4=p/36 | | 3x-0.3(6-x)=3.9 | | -6=28b | | 8x+1=9x-6 | | 8/x=4/6 | | 154=-7(6+7x) | | 4x+145=137 | | 16=-5+z/4 | | 2m=28 | | 2x^4+22x^3+56x^2=0 | | (X^2+5)^(1/2)=3-x | | 8x-(6x+4)=4 | | 4x+145=181 | | -2s+18-4d=60 | | 2x+3(x-5)=4x-6 | | 4x+145=188 | | 4x-(8x+8)=3x-43 | | 12x-4(5y-2x)=90 | | y^2+9y=8 | | 48=c/9 | | z-m=z+b | | 11(3-x)=55 | | 4x*9=-2x+4 | | -32r=-310 | | -5(7+6m)-2m=-291 | | 3x^(3/4)=192 | | (2m^3)(4m^2)=0 | | d/-56=-23 |